Забезпечення фінансово-економічних потреб населення як напрям діяльності органів місцевого самоврядування та української кооперації (кінець XIX — початок XX ст.) - Лисенко, О.В. (Проблеми історії України ХІХ – початку ХХ ст., 2017)
У статті висвітлюється роль української інтелігенції, котра складалася
переважно з представників старої козацької старшини. Вони, займаючи високі
посади в офіційних імперських структурах, таких, як земства, разом з тим
активно працювали над покращенням умов життя українського народу, задоволення його реальних соціально-економічних та національно-культурних й освітніх проблем. Це досягалося активною підтримкою української кооперації,
яка своєю чергою фінансувала культурно-освітні потреби населення, сприяла
розповсюдженню серед селянства як спеціальної сільськогосподарської літератури, так і творів провідних українських письменників. У земствах та кооперативах українці вчилися вести реальну господарську економічну діяльність, у них формувалися нові кадри для розвитку української економіки на ринково-демократичних засадах, котрі повинні були поступово замінити як
наскрізь просякнуту бюрократизмом російську напівфеодальну економіку, так і
великий західноєвропейський капіталізм. На жаль, цей надзвичайно важливий
для подальшої долі України процес загальмувала Перша світова війна, яка
забрала життя багатьох українських земців і кооператорів. Тому, коли волею
долі в 1918 р., у часи правління гетьмана П. Скоропадського вцілілі колишні
земці та кооператори стали на чолі відродженої Української Держави, вони не
змогли цілком виконати ті складні завдання, що постали перед ними в цей важкий і переломний для країни період. Також далася взнаки непідготовленість учорашніх земців та кооператорів до масштабної державотворчої праці. Не
дивлячись на це, вони зіграли важливу позитивну роль в історії України, а їхня діяльність потребує всебічного дослідження. The article shows the role of the Ukrainian intelligentsia which consisted mainly
of representatives of the old Cossack elder. They held high positions in official
imperial structures such as, for example, zemstvo, at the same time they actively
worked to improve the living conditions of the Ukrainian people, to meet their real
socio-economic and national-cultural and educational problems. That was achieved
by an active support of Ukrainian cooperation which, in turn, financed cultural and
educational needs of the population, contributed to the spread of peasantry, special
agricultural literature and works of leading Ukrainian writers. In zemstvo and
cooperatives Ukrainians learned to carry out real economic activities, they created
new staff for the development of the Ukrainian economy on a market-democratic
basis, which supposed to gradually replace the half-feudal Russian economy
infiltrated by bureaucracy and the colonial West European capitalism, which
hampered the socio-economic development of the Dnieper region. Unfortunately, this
extremely important process for the future of Ukraine was hampered by the First
World War, which took away the lives of many Ukrainian from zemstvo and
cooperatives, who went to the front and died there being law-abiding citizens of the
Russian Empire. Therefore, as fate willed in 1918, at the epoch of Hetman
P. Skoropadsky, the survived members of zemstvo and cooperatives headed the revived
Ukrainian state, they were not able to completely fulfill difficult tasks they were facing
in this difficult and crucial period for the country. Also, there attributed the unpreparedness
of yesterday’s peasants and co-operators to large-scale state-building work
and, unfortunately, certain class constraints and selfishness which were used by
Ukrainian socialists, who, with the help of populist and anti-Semitic slogans,
overthrew Hetman P. Skoropadsky, thereby opening the way to Russian Bolshevism. Despite these mistakes, Ukrainian peasants and co-operators played an extremely important positive role in the history of Ukraine and their activities require a thorough study.